The jungle book - Ainsworth, Alison; Bernstein, Galia Kipling, Rudyard (Ladybird London, 2013)
The Jungle Book has been sensitively abridged and retold to make it suitable for sharing with young children, while retaining all the key parts of the story including Mowgli's life in the Jungle, his battle with Shere Khan, and fascinating details about learning to live with humans once more